Analysis Of Acceptance And Profits Of The Tempe Household Industry - Nindianata Sekar Adil; Eko Sumartono; Yossie Yumiati (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2024)
Purpose : The aim of this research is to determine the advantages and acceptance obtained by each owner of home-based tempeh industries located in Sukaraja District. Method: The research conducted in Sukaraja District used a sampling method that took certain considerations into account, namely the duration of the business (10 years) and the production volume (500 kg per month). After consideration, the number of respondents obtained was 5 (five) respondents. Quantitative research, the data obtained in the field is processed using Microsoft Excel. Results: This study presents the revenue of home-based tempeh industries in Sukaraja District for the month of April, with an average revenue of Rp.23,325,000. Poernomo's tempeh industry generated a revenue of Rp.29,935,000, Randat earned Rp.24,450,000, Salim Rp.22,960,000, Saumi Rp.21,480,000, and Agil's industry earned Rp.17,800,000. The profits obtained from the five home-based tempeh industries are as follows: Poernomo's Rp.11,890,698, Randat's Rp.7,371,032, Salim's Rp.7,806,869, Saumi's Rp.6,085,774, Agil's Rp.4,295,209, with an average profit of Rp.7,489,916. Findings: Success acceptance highest can be attributed to several key factors, including operational efficiency and greater economies of scale and greater economies of scale Novelty: This study provides new insights into the profits earned by tempeh artisans in Sukaraja sub-district. Sukaraja sub-district. Originality: This study offers an analysis of the profitability of the household-scale profit analysis of the household-scale tempeh industry in Sukaraja District. Conclusion: It can be seen that the income and profits obtained by the owners of this home-based tempe industry are very beneficial for them. Type of paper : Empirical Research Article